2010
DOI: 10.4314/ijest.v1i1.58064
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analysis of Thyristor and IGBT based induction motor soft starters

Abstract: In this paper the performance of a split-phase motor and a three-phase induction motor drives for soft starting is evaluated. The paper systematically investigates and compares the characteristics of a variable voltage fed induction motor drive for two different types of soft starters; one based on IGBT and another based on Thyristor. Experimental validation is done using analogue circuit based system, developed in the laboratory. The novelty of the work lies in the development of simple and flexible models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…6, it is concluded that for all the carrier signal frequencies (except 60 Hz) % THD of IGBT inverter output voltage is higher than MOSFET inverter. As in this design no harmonic filter is used, so overall %THD of IGBT inverter is higher than MOSFET inverter, since IGBTs result in large amount of harmonic distortion in output voltage of inverters, so IGBTs should not be used as power switch without harmonic filters [7].…”
Section: Discussionmentioning
confidence: 99%
“…6, it is concluded that for all the carrier signal frequencies (except 60 Hz) % THD of IGBT inverter output voltage is higher than MOSFET inverter. As in this design no harmonic filter is used, so overall %THD of IGBT inverter is higher than MOSFET inverter, since IGBTs result in large amount of harmonic distortion in output voltage of inverters, so IGBTs should not be used as power switch without harmonic filters [7].…”
Section: Discussionmentioning
confidence: 99%
“…(1) it is evident that the torque produced is proportional to the square of the applied voltage (T 1 αV 1 2 ). And if the motor is applied with full rated voltage then the motor is accelerated suddenly and the sudden acceleration may cause mechanical stresses in the parts of the motor as well as the associated mechanical linkages [7,8]. Huge starting currents may heat up the motor and also because of sudden increase in currents the feeder voltages may dip affecting other voltage sensitive loads connected to the same feeder [9].…”
Section: Methodsmentioning
confidence: 99%
“…AC choppers, which are control systems for AC machines based on thyristors (SCR) used for soft starting, regulate the voltage supply during machine startup, reducing startup currents [36][37][38]. However, a decrease in torque is observed since it is proportional to the square of the current.…”
Section: Introductionmentioning
confidence: 99%